Culture’s Effect on Communication - Hamdar, Ali (My University, 2012)
Sweden has transformed from a homogeneous society into a society with over one hundred nationalities, languages, different religions and beliefs. Swedish people and companies are establishing business abroad. The importance of extended knowledge about other cultures is becoming essential for all the parties. The purpose of this thesis was to illuminate the interaction between the people from the different cultures. The study was based on a qualitative approach both for data collection and analysis of the data. A qualitative interview with open questions was used to explore the informants’ experience of the phenomenon. The informants consisted of 6 persons, 3 Swedes and 3 Asians who are working in Matrix shipping, a UAE based shipping company. The results from the interviews with these different persons showed that most of the participants felt that they faced some problems with colleagues from different cultural background because they do not share the same culture and language. Both the Swedes and the Asians which experienced difficulties in understanding their colleagues and that colleague’s didn´t understand them properly due to cultural differences, felt frustration of not being understood or not to understand the colleagues. They felt that understandable behavior was essential to good communication. The focused group felt a need to increase their knowledge about the other cultures. The conclusion of the study was that differences in culture, expectations and attitudes affect how people experience the work and the environment in different working places. The more adequate information and knowledge the informants had about the other cultures and awareness about their difference, the less misunderstanding and conflicts occurred. The knowledge could be gained by training the employees at the different companies in cultural differences and how to deal with them in a positive way to utilize the synergy and deal with the differences between various cultures. II I advise a study on how to train people who is working in shipping related business to deal with people from other cultures. Such a study could arm the employees with better confidence to deal with the variations and differences.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering